2013
DOI: 10.21273/horttech.23.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Cost of Cultivators, Steam, or an Organic Herbicide for Weed Control in Organic Vineyards in the San Joaquin Valley of California

Abstract: Weed management is an important problem faced by organic grape (Vitis vinifera) growers as there are few effective and economic options available. However, new organically acceptable weed control products have become available in recent years. Several studies were conducted to compare the efficacy of two mechanical weed control methods (French plow and Bezzerides tree and vine cultivator) with steam, and an organic herbicide (d-limonene) in organic raisin and wine grape viney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In addition, some authors have also reported that growth of certain weeds can even be stimulated by tillage [ 33 ]. Nevertheless, mechanical tillage was observed to provide slightly better weed control than organic herbicides, as reported in other studies [ 16 ]. In our trial, wood chips worked better than mechanical tillage in terms of weed-free area.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In addition, some authors have also reported that growth of certain weeds can even be stimulated by tillage [ 33 ]. Nevertheless, mechanical tillage was observed to provide slightly better weed control than organic herbicides, as reported in other studies [ 16 ]. In our trial, wood chips worked better than mechanical tillage in terms of weed-free area.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, more frequent sprays might have increased the effectiveness of the limonene, soap, and even caprylic acid treatments. Limonene has been reported to provide very efficient weed control in almond orchards in California [ 17 ], whereas poor results were observed in vineyards, with acceptable control lasting only 2–3 weeks [ 16 ]. The need for more frequent treatments for effective control of organic herbicides has likewise been suggested [ 17 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such tests, a different methodology for weed biomass assessment might be recommended. The method used in this study and in previous research [9,13] has the disadvantages of being destructive, thus increasing data variability, and time-consuming. Visual assessment of ground covered by the weeds, coupled with digital image analysis [10,14], while appropriate to assess treatments aiming at a complete removal of the weeds, as in most field crops experiments, seems hardly suited for permanent crops, when the purpose is just to reduce weed competition, because of the difficulty of establish a correlation between the ground area covered by the weeds and their actual biomass.…”
Section: The Field Testsmentioning
confidence: 99%
“…Another increasingly used weed control method is thermal weed control. Thermal weed control can be used in various crops (Shrestha et al, 2013;Velička et al, 2016) In different countries, diverse methods of thermal weed control are used in organic farms: flaming (Sivesind et al, 2012), combustion gases (Ulloa et al, 2010;2012;Datta, Knezevic, 2013), hot foam (Cederlund, Börjesson, 2016), hot water (De Cauwer et al, 2014) and water steam (Melander, Kristensen, 2011;Shrestha et al, 2012;Vidotto et al, 2013). Researchers have indicated that thermal weed control is more effective than mechanical weed control (Virbickaitė et al, 2006;Ascard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%